1998
DOI: 10.1002/(sici)1096-9101(1998)23:3<151::aid-lsm4>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced laser thrombolysis with photomechanical drug delivery: An in vitro study

Abstract: Background and Objective: Current techniques for laser thrombolysis are limited because they can not completely clear thrombotic occlusions in arteries, typically leaving residual thrombus on the walls of the artery. The objective of this study was to investigate the possibility of using photomechanical drug delivery to enhance laser thrombolysis by delivering drugs into mural thrombus during laser thrombolysis. Study Design/Materials and Methods: Three experimental protocols were performed in vitro to quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Laser radiation can potentially be used to deliver drugs into thrombus or increase permeability of cell membranes. It was demonstrated that drugs can potentially be delivered photomechanically into thrombus on the walls oflarge arteries with the use ofmicrosecond laser pulses [28,29]. The laser pulses can be delivered into the arteries through fiber-optic catheters and induce millimeter-sized bubble expansion and collapse.…”
Section: Discussionmentioning
confidence: 99%
“…Laser radiation can potentially be used to deliver drugs into thrombus or increase permeability of cell membranes. It was demonstrated that drugs can potentially be delivered photomechanically into thrombus on the walls oflarge arteries with the use ofmicrosecond laser pulses [28,29]. The laser pulses can be delivered into the arteries through fiber-optic catheters and induce millimeter-sized bubble expansion and collapse.…”
Section: Discussionmentioning
confidence: 99%
“…A localized drug delivery, termed photomechanical drug delivery, has been reported by Shangguan et al 59 They demonstrated that hydrodynamic flow and pressures resulting from formation, expansion, and collapse of laser induced bubbles can be the driving force for facilitating drug delivery. 59 Apart from bubbles, a liquid jet can also be formed via laser irradiation. For example, Hirano et al reported that a liquid jet formed through Ho:YAG laser irradiation within a water-filled catheter could promote fibrinolysis by means of delivering fibrinolytic agents into the thrombus.…”
Section: Light-sensitive Tddsmentioning
confidence: 99%
“…21 This effect may be due to the increased surface area of clot exposed to the thrombolytic agent. 22 However, the inability to navigate mechanical devices through small blood vessels to the target areas limits this approach. Furthermore, large fragmented particles of clot may lead to undesirable occlusion of distal branches.…”
Section: Mechanical Thrombolysismentioning
confidence: 99%